Design and exploitation of cadaverine metabolic pathway for simple N-heterocyclic chemical production. - Anyanwu, Valentine E. (2019)
Nitrogen-heterocycles are widely found in nature as subunits of compounds from secondary metabolism (vitamins, alkaloids, hormones etc.) and are valuable building blocks to manufacture a wide range of pharmaceuticals, agrochemicals, flavours and fragrances. Currently, N-heterocycles are produced through unsustainable chemical processes that rely on petrochemical feedstocks and high-energy consumption. The six-membered simple N-heterocycle Δ¹-piperideine (2,3,4,5-tetrahydropyridine), is a key building block for biosynthesis of some alkaloids, for example, the piperidine, quinolizidine, indolizidine and lycopodium alkaloids. Δ¹-piperideine also has considerable promise as a platform compound for chemical synthesis of functionalized or complex compounds with economic importance. Although the bioproduction of complex, functionalised N-heterocycles have been reported, bioproduction of unsubstituted simple N-heterocycles have not yet been achieved. Advances in metabolic engineering and synthetic biology offers an approach to develop bioprocesses for sustainable production of simple N-heterocycles from renewable sugar feedstocks. Δ¹-Piperideine can be obtained by oxidation of cadaverine using amine oxidases or transaminases, to yield 5-aminopentanal. This product is known to cyclise spontaneously into Δ¹-piperideine. However, Δ¹-piperideine reacts spontaneously in aqueous solution to form the multimeric products (tetrahydroanabasine, α-tripiperideine and isotripiperideine). Therefore, the suitability of putrescine oxidase from Rhodococcus erythropolis (PuORh) for cell-free and whole-cell bioproduction of Δ¹-piperideine was studied. PuORh was characterised for the first time by monitoring oxygen concentration in a direct substrate consumption assay. Using purified PuORh and PuORh induced whole cells; the conversion of cadaverine to Δ¹-piperideine was demonstrated qualitatively and quantitatively. This study indicates that PuORh is suitable for the bioproduction of Δ¹-piperideine. Finally, a metabolic route has been designed and proposed for whole cell bioproduction of Δ¹-Piperideine from renewable feedstocks.